Application of Optimization Theory in Planning the Use of Idle Land for Agriculture - Een Mardiyanti; Kania Ari Liany (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
: This study aims to apply optimization theory in planning the use of idle land for agriculture to improve efficiency and farmers' income. This study was motivated by the existence of underutilized idle land and limited agricultural resources, which often result in inefficient land use and suboptimal income for local farmers. A case study was conducted on a 1,000 m² plot of idle land in Highland Park Housing, Kota Serang Baru, Serang, Banten, using a quantitative approach and Linear Programming (LP) analysis. Primary data were collected through interviews and field observations, while secondary data were obtained from the literature and relevant sources. The results showed that cucumbers and small chili contributed the most to income, with optimal land allocations of 900 m² and 100 m², respectively. Chili pepper and eggplant were not economically feasible for cultivate under the current conditions because of their low profitability. By applying LP through Excel Solver, the maximum income obtained was Rp71,600,000. Chilli pepper cultivation is recommended based on simple analysis and linear programming due to its significant and optimal profits. The study concludes that optimization theory provides an effective approach for the sustainable planning of idle land use in agriculture.